Bahan Bangunan dalam Peradaban Manusia: Sebuah Tinjauan dalam Sejarah Peradaban Manusia - Gatot Suharjanto (Bina Nusantara University, 2011)
Building, which consists of many building materials arranged in following the designer’s patter, could be stood and built in many scale, time and place. Development of the shape in building design has been changed from time to time as in time development and human ability that keeps increasing. Many buildings came from human civilization. Knowledge, social community and environment circumstances and also building material sources have huge role in developing building shapes. How far the existance of the building, it becomes retrieval benchmark in human civilization through building material usage approach in each age.